Transforming Value of National Character Through Nahdlatul Ulama Organization In Perspective of Civic Education - Rizqi, Ascosenda Ika; Sapriya, Sapriya; Abdulkarim, Aim; Sundawa, Dadang (Jurnal Moral Kemasyarakatan, 2025)
Civic education becomes a curriculum with the aim of forming good, intelligent citizens as well as value education. One of the roles of civic education is through community civics. Community Civics has a character that is not value-free, specifically in the context of the community can encourage young citizens as pioneers of national independence. Community Civic is through community organisations. The role of community organisations (CSOs) is necessary because it can help maintain the sovereignty of the country as a whole. The community organisation that plays a role in maintaining national values is Nahdlatul Ulama (NU). The presence of community organisations is present because Indonesia's problems now lead to an order that is not in line with the values of life in citizens and the presence of community organisations is expected to help maintain the sovereignty of the country as a whole. Community organisations can be relevant to Community Civic Education which aims to form citizens who are proud of their own nation. This research method is discussed from an ethnographic point of view in order to analyse a group along with the behaviour in their daily lives. The results of the concept of transformation of the value of Civic Education in the form of national values that can be actualised in the Nahdlatul Ulama (NU) organisation are 5 of them: Reform Value, Balance Value, Tolerance Value, Good Citizen Value and Moderate Thinking Value.